Character Education in the Era of Technological Development and Advancement - Marhamah; Zikriati; Baharuddin; Miratil Hayati; Rahmat Saputra; Hanifuddin (International Journal of Education, Language, and Social Science, 2026)
The advancement of technology presents both opportunities and challenges for education. While technology supports learning processes, uncontrolled use can negatively affect behavior, particularly among adolescents. Ethical use of technology enhances learning efficiency, curriculum attainment, creativity, and student autonomy. Conversely, excessive and unrestricted use can cause moral decline, reduced social interaction, misuse of digital tools, and diminished critical-thinking skills, which in turn weaken motivation and academic achievement. In this context, character education is a crucial element for shaping an integrity-driven younger generation amid rapid globalization and digital transformation. This study employed a literature-review approach, analyzing sources through data reduction, thematic categorization, interpretation, and synthesis. Findings indicate that character education provides a foundational basis for developing morally responsible, dignified, and honorable youth, exemplified by the prophetic mission of Prophet Muhammad (peace be upon him). Effective implementation requires collective responsibility from schools, families, communities, and government. Strong collaboration among these stakeholders will create a civilized, respectful, safe, and harmonious environment that supports the development of resilient, intelligent, high-achieving, and responsible generations. Integrating character values into the curriculum, promoting exemplary role models, strengthening parental involvement, and enhancing digital literacy are effective strategies to cultivate a generation equipped with robust character values in the digital era